2022
DOI: 10.1097/mrr.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

Is robot-assisted gait training intensity a determinant of functional recovery early after stroke? A pragmatic observational study of clinical care

Abstract: Gait rehabilitation is a critical factor in functional recovery after a stroke. The aim of this pragmatic observational study was to identify the optimal dose and timing of robot-assisted gait training (RAGT) that can lead to a favourable outcome in a sample of subacute stroke survivors. Subacute patients with stroke who underwent a RAGT within a multidisciplinary rehabilitation program were enrolled. A set of clinical (i.e. age, type of stroke and time since stroke) and rehabilitation stay outcomes (length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
(67 reference statements)
0
12
1
Order By: Relevance
“…Regarding the optimal amount and timing of robot training using Locomat in stroke patients have reported that younger age, early intervention after injury, and higher training doses (at least 14 sessions) are associated with better outcomes [ 44 ]. In the present study of young neurological patients, fewer doses (12 sessions) could lead to statistically significant differences in walking ability and gross motor function.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the optimal amount and timing of robot training using Locomat in stroke patients have reported that younger age, early intervention after injury, and higher training doses (at least 14 sessions) are associated with better outcomes [ 44 ]. In the present study of young neurological patients, fewer doses (12 sessions) could lead to statistically significant differences in walking ability and gross motor function.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that people with stroke who receive robot-assisted gait training in combination with standard physical therapy achieve positive effects in terms of independent walking, as compared with those receiving only conventional gait rehabilitation training [ 19 ]. However, several studies have reported inconclusive results regarding the efficacy and potential indications of using robotics alone in both acute and chronic stroke [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Additionally, a variety of devices and treatment duration and frequency contribute to the wide variability in outcomes across studies [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study was designed with the aim of assessing the clinical effects of robot-assisted gait training compared with conventional training in subacute stroke patients. Considering that gait speed is a key indicator of post-stroke gait performance and has considerable importance on disability burden reduction [ 25 ], we hypothesized that gait speed would improve most in subjects who received an effective number of robot-assisted gait training sessions (a total of 20 sessions) [ 26 , 27 ] versus those treated with overground gait training. As a secondary analysis of data from patients receiving robot-assisted gait training, we compared the effects of the two types of stationary robotic devices.…”
Section: Introductionmentioning
confidence: 99%
“…In this inaugural year, the Editor’s Choice articles were from Slovenia, Italy, Brazil, and the USA: March: Rehabilitation of COVID-19 patients with respiratory failure and critical illness disease in Slovenia: an observational study [1] June: Is robot-assisted gait training intensity a determinant of functional recovery early after stroke? A pragmatic observational study of clinical care [2] September: Constraint-induced movement therapy for lower extremity use in activities of daily living in people with chronic hemiparesis: multiple case study [3] December: Cognitive impairment predicts engagement in inpatient stroke rehabilitation [4] …”
mentioning
confidence: 99%
“…June: Is robot-assisted gait training intensity a determinant of functional recovery early after stroke? A pragmatic observational study of clinical care [2]…”
mentioning
confidence: 99%